Design, analysis and fabrication of pedal powered washing machine / Azlan Shah Kamarul Kalai - Kamarul Kalai, Azlan Shah (2023)
This project is to help people to save money, save time, and for people who lives in rural area. Due, to people who lives in rural area don’t usually have stable electricity and to cut their cost for laundry because it relates with electric and water bills. The objectives for this project are to design and analysis an efficient pedal powered washing machine and to fabricate the pedal powered washing machine similar according the design made. Then, the methodology that been use is Morphological Analysis to generate the final design, internet for research and journals as my guidance to ease my work. The results that should appear is how the machine can function well and it’s fabrication. In conclusion, this project should succeed it’s fabrication and the dissertation as expected in within this semester